Comparative Analysis on Segmentation Approaches for Plant Leaf Disease Detection - Vijayalakshmi, S; Murugan, D (International Journal of Computer Sciences and Engineering, 2025)
Plant pathology is the scientific analysis of plant diseases caused by pathogens and different environmental conditions. The leaf is one of the significant plant parts which highlight the presence of diseases. Existing methods use spectroscopic techniques to detect the diseases present in plants. These techniques are very expensive and can only be utilized by trained persons only. The method mentioned in this paper is an easy and cost-effective way which utilizes the leaf image of the plant. This input image is subjected to segmentation of disease part, feature extraction and classification in order to identify the disease. The main objective of this paper is to compare the clustering approaches FCM, Artificial Bee Colony and K-Means which are useful in disease part segmentation and to identify the best approach yields accurate results for identifying the plant disease. This work utilizes the GLCM, Run Length, Color Moment and Color Histogram features for feature extraction. Once these features are extracted from the segmented disease part, the disease present in the leaf is identified using the KNN (K- Nearest Neighbor) technique. The experimental result shows that the Artificial Bee Colony approach segments the diseased part of the leaf in a better way than the other two approaches.